Transitional justice mechanisms under the African human rights system : prospects and challenges for countering massive human rights violations in Cameroon - Wondemagegn, Tadesse (University of Pretoria, 2021)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2021.